Revisiting Spanish Revisable Permanent Prison: Its Context Surroundings, the Constitutional Court Judgment Endorsing It, and Its Intended Reform Project - Martín Aragón, María del Mar (2023)
This paper addresses the new problems arisen after the recent judgement from the Spanish Constitutional Court ratifying revisable permanent prison. We need to bear in mind that Constitutional Law 1/2015 introduces permanent revisable prison for the very first time in the Spanish sentencing system. This sentence faced serious problems of constitutionality that were highlighted by a report made by a group of experts that would serve as a basis for the action of unconstitutionality presented in June the 30th 2015. It has taken six years for the Constitutional Court to solve this action in the sadly predictable sense to consider this penalty as constitutional; nevertheless, three dissenting votes pointed in the opposite direction. This decision has left an open door that certain political parties have decided to take and advantage of, in a punitive turn to extend this revisable permanent prison to new criminal situations. So, this work seeks to analyze the ramifications of this judgement, contributing to the reflection on permanent revisable prison and its escalation, so as the problems that it raises.